Prevalence of Proximal Contact Loss between Implant-Supported Prostheses and Adjacent Natural Teeth: An Umbrella Review - Fathi, Amirhossein; Mosharraf, Ramin; Ebadian, Behnaz; Javan, Mehdi; Isler, Sabire; Dezaki, Sara Nasrollahi (European Journal of Dentistry, 2022)
Contact loss between the implant prosthesis and adjacent natural teeth is a clinical complication whose overall prevalence is uncertain. Therefore, the main purpose of this umbrella study was to evaluate the extent of contact loss between implant prostheses and adjacent natural teeth. Electronic database of MEDLINE/PubMed, Cochrane, and Google Scholar was searched until August 2021 without considering language restrictions and according to Preferred Report Items for Systematic and Meta-Analysis guidelines (preferential reporting items for systematic review and meta-analysis). Inclusion criteria were systematic/meta-analysis review articles related to contact loss between implant prostheses and adjacent natural teeth. Inclusion criteria and risk of bias for the selected systematic/meta-analysis review studies were assessed by two or three qualified researchers, and the fourth researcher was used to resolve the ambiguities. From 43 eligible articles, five systematic/meta-analysis review studies were selected for this study. Important information such as the range of contact points, the prevalence, and the location of the contact loss was extracted. Three research studies had a low risk of bias and were considered clinical evidence. Analysis of low-risk studies showed that the superiority of open contact loss was excessive. Prevalence of proximal contact loss was more in mesial contact, especially in the mandibular arch. No significant differences were reported in sex or between the posterior and anterior regions.
Keywords: proximal contact loss; implant-supported prostheses; adjacent natural teeth